Patterns of Recurrence and Survival Rate After Complete Resection of Pathological Stage N2 Small-Cell Lung Cancer - Yu, Lian; Xu, Jianlin; Qiao, Rong; Zhong, Hua; Han, Baohui; Zhong, Runbo (Frontiers in Oncology, 2021)
The benefits of surgical resection for patients with stage N2 limited disease small-cell lung cancer (LD-SCLC) remain controversial. This retrospective study analyzed the survival and recurrence patterns of the patients diagnosed with pathological N2 (p-N2) LD-SCLC after radical resection. A total of 171 p-N2 LD-SCLC patients who underwent radical pulmonary resection and systematic lymphadenectomies at Shanghai Chest Hospital from July 2005 to June 2015 were enrolled. The influence of the mediastinal lymph node status (single or multiple nodes, single- or multiple-station) on the survival and recurrence patterns was retrospectively analyzed. The main recurrence sites were outside the chest cavity (54.8%) and hematogenous metastasis (67.4%). The bone and liver as initial recurrence sites had a poor prognosis, with a median overall survival (OS) 13.100 months and 11.900 months, respectively. The median disease-free survival (DFS) of patients diagnosed with single and multiple p-N2 after surgery were 19.233 and 9.367 months (P=0.001), and the median OS were 43.033 and 17.100 months (P<0.001), respectively. In conclusion, recurrence occurred in the form of hematogenous metastasis mostly in the extra-thoracic part. Interestingly, patients diagnosed with single p-N2 benefited from radical resection. Surgery may be a treatment option regardless of the T stage if N2 SCLC with a single metastatic lymph node can be identified preoperatively.